Literature Review: The Long-Term Use Effect of Proton Pump Inhibitors and The Risk of Fractures - Fatharani, Adelia; Hilmi, Indah Laily (Jurnal EduHealth, 2022)
Proton Pump Inhibitors (PPIs) are a group of drugs widely used to treat gastrointestinal disorders. Long-term use of PPIs has a risk of several side effects, one of them is fractures. The aims of this study is to examine the relationship between long-term PPIs use and the risk of fractures. The method in this literature review was literature study by searching for research article through Google Scholar and Pubmed Central by using the keywords "Proton pump inhibitors, Long-term use, Risk, Fracture". An analysis of 10 selected journals was conducted and concluded that the long-term use of PPIs has a risk of fracture.